Discovery of spirohydantoins as selective, orally bioavailable inhibitors of p300/CBP histone acetyltransferases. (1st May 2021) - Ji, Zhiqin; Clark, Richard F.; Bhat, Vikram; Matthew Hansen, T.; Lasko, Loren M.; Bromberg, Kenneth D.; Manaves, Vlasios; Algire, Mikkel; Martin, Ruth; Qiu, Wei; Torrent, Maricel; Jakob, Clarissa G.; et al.
Graphical abstract: Abstract: p300 and CREB-binding protein (CBP) are essential for a multitude of cellular processes. Dysregulation of p300/CBP histone acetyltransferase activity is linked to a broad spectrum of human diseases including cancers. A novel drug-like spirohydantoin (21 ) has been discovered as a selective orally bioavailable inhibitor of p300/CBP histone acetyltransferase. Lead compound 21 is more potent than the first-in-class lead A-485 in both enzymatic and cellular assays and lacks the off-target inhibition of dopamine and serotonin transporters, that was observed with A-485.